2023
DOI: 10.1101/2023.10.06.561186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PKCδ is an activator of neuronal mitochondrial metabolism that mediates the spacing effect on memory consolidation

Typhaine Comyn,
Thomas Preat,
Alice Pavlowsky
et al.

Abstract: Relevance-based selectivity and high energy cost are two distinct features of long-term memory (LTM) formation that warrant its default inhibition. Spaced repetition of learning is a highly conserved cognitive mechanism that can lift this inhibition. Here, we questioned how the spacing effect integrates experience selection and energy efficiency at the cellular and molecular levels. We showed in Drosophila that spaced training triggers LTM formation by extending over several hours an increased mitochondrial me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 93 publications
1
5
0
Order By: Relevance
“…Similar to rodent neurons in vitro (Figure 2J, K), we quantified pyruvate accumulation rates in vivo as a readout of cytosol-to-mitochondria pyruvate flux by blocking mitochondrial pyruvate import 15 (Figure 3D). We confirmed that 3 hours after 1x training, mitochondrial pyruvate import was not accelerated in α/β neurons of wild-type flies (Figure 3D, left panel), as previously reported 68 . To examine the effect of reducing Letm1 expression in this paradigm, we expressed Pyronic together with an RNAi conditionally targeting Letm1 exclusively in adult α/β neurons in adults 74 (see Materials and Methods).…”
Section: Letm1 Controls Neuronal Metabolism In Vivo Governing Long-te...supporting
confidence: 91%
See 4 more Smart Citations
“…Similar to rodent neurons in vitro (Figure 2J, K), we quantified pyruvate accumulation rates in vivo as a readout of cytosol-to-mitochondria pyruvate flux by blocking mitochondrial pyruvate import 15 (Figure 3D). We confirmed that 3 hours after 1x training, mitochondrial pyruvate import was not accelerated in α/β neurons of wild-type flies (Figure 3D, left panel), as previously reported 68 . To examine the effect of reducing Letm1 expression in this paradigm, we expressed Pyronic together with an RNAi conditionally targeting Letm1 exclusively in adult α/β neurons in adults 74 (see Materials and Methods).…”
Section: Letm1 Controls Neuronal Metabolism In Vivo Governing Long-te...supporting
confidence: 91%
“…A short 1x training session causes a quick rise in pyruvate absorption by mitochondria 67 that is temporary and no longer detectable three hours after conditioning 68 . The 5x spaced training, in contrast, leads to an extended period of metabolic activation observable up to 8 hours after conditioning 68 . This long-lasting upregulation in the metabolic state of MB neurons is a critical early step that enables the formation of LTM 15 .…”
Section: Letm1 Controls Neuronal Metabolism In Vivo Governing Long-te...mentioning
confidence: 99%
See 3 more Smart Citations